Peningkatan Pengetahuan Nutrisi untuk Tumbuh Kembang Anak Guna Menurunkan Angka Stunting di Desa Gebyog Mojogedang Karanganyar - Mustofa, Akhmad; Suhartatik, Nanik (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2023)
Stunting was a major problem in the development progress and must be resolved immediately. Karanganyar as one of the districts in Central Java province that has a stunting rate of 5.86% (2021). Even this number was lower than the national average for stunting, it must be handled with care so that Indonesia can be free from stunting. Mojogedang as one of the sub-districts in Karanganyar has the highest stunting rate compared to other sub-districts. Of all the villages in the Mojogedang, Gebyog is the village with the highest stunting rate in the Mojogedang sub-district, even the highest in Karanganyar Regency in 2021. Personal approach to provide understanding and also the actions needed to eradicate stunting is the goal of the program. The service was carried out by the community service team. The purpose of this activity was to increase the knowledge of pregnant women or prospective mothers about nutrition for pregnant and lactating women. The activity was carried out by recording the number of stunting sufferers, followed by conducting counseling for early marriage, nutrition for pregnant and lactating women, and the effect of stunting on children's conditions. The activity ended with the provision of additional food to families of stunting sufferers. Based on observations made in the field, the factors causing stunting in Gebyog Village were the lack of knowledge about nutrition for pregnant or lactating women and the number of early marriages. Although poverty is also a contributing factor, with the dominance of the population being farmers, the community is able to provide healthy and nutritious food every day. Handling stunting should be based on the problems and natural potentials that exist in the region and involve all fileds